The implementation of eco-labelling for construction materials in Malaysian construction industry - Hosseini, Seyedmohsen (2013)
In response to sustainable development and green initiatives, many tools have been developed for building development. Eco-labelling (Green labeling or Environmental labeling) began as part of “Green Revolution” in marketing with non-food products. Environmental labeling refers to labels that inform consumers that a labeled product is more environmentally friendly relative to the other products in the same category. Eco-labels are designed to inform consumers that the labeled product is more environmentally friendly than most typically setting standards. In addition, Eco-labels are increasingly facilitating manufacturers, retailer, consumers, government officials, and other interested parties with information in their purchasing decision. Eco-labelling is one of the assessment tools that comes as third-party and has a serious role to verify eco-friendly products and compatible with the environment. This study therefore interested to identify the suitable strategy need to be employed in construction industry and suggest the solution for solving the problems of the current eco-labelling innovation in construction materials. This study aims to study the current gaps and potential linkages in implementation of Eco-labelling in Malaysia. Therefore, pilot survey conducted through the questionnaire and interview process with developers, suppliers, contractors, consultant and other construction companies that are regarded as consumers of eco-labelling materials. As a result, the cost of implementation, irrelevant standards for certificating, lack of users' awareness, poor coordination and consistency between rating tools and regulation are as critical barriers and problems. In overall, reliability & quality of rating system for construction materials, leadership & responsibility of conducting eco-labelling schemes in construction industry, and stakeholders involvement are most critical gaps toward eco-labelling.